Reflections on the Science Centre Education Officers as They Enhance the Teaching and Learning of Science - Bilankulu, Hasani J.; Mudau, Awelani V.; Ntuli, Thuli G. (Unnes Science Education Journal, 2023)
This qualitative interpretative case study explored in detail the use of exhibits to enhance the teaching and learning of science by a science centre in Pretoria, South Africa. The study was guided by the following research question: what are the reflections on the science centre education officers as they enhance the teaching and learning of science? Two education officers were purposefully sampled as participants in this study. Data were collected through observation and semi-structured interviews. Findings revealed that indeed exhibits are the major component of the science centre, however, some education officers do not have the content knowledge (CK) of the exhibits, some visiting schools do not understand the use of the exhibits to enhance the teaching and learning of science. It is recommended that education officers should receive proper training on the content knowledge of the exhibits and visiting schools must be encouraged to fully participate in the teaching and learning at the science centre. Teacher’s workshop should be coordinated to encourage teachers to use the exhibits for teaching and learning at the centre. School curriculum should include visits to science centres for practical projects to enhance the teaching and learning of science.